Pharmacokinetics, tolerability, and safety of ACP-103 following single or multiple oral dose administration in healthy volunteers - Vanover, Kimberly E; Robbins-Weilert, Doris; Wilbraham, Darren G; Mant, Timothy G K; van Kammen, Daniel P; Davis, Robert E; Weiner, David M (Journal of clinical pharmacology, 2007)
The pharmacokinetics, safety, and tolerability of ACP-103, a selective serotonin 5-HT(2A) receptor inverse agonist, were evaluated in 2 double-blind, placebo-controlled, dose escalation studies in healthy male volunteers. Pharmacokinetic sampling was measured up to 216 hours after single oral/nasogastric doses of ACP-103 and after the last dose of once-daily oral administration of ACP-103 for 14 days. Single doses of ACP-103 (20-300 mg) resulted in dose-proportionate mean C(max) values (9-152 ng/mL) and AUC(0-infinity) (706-10 798 h x ng/mL), and multiple doses (50-150 mg) resulted in dose-proportionate mean C(max,ss) (93-248 ng/mL) and AUC(0-infinity,ss) (1839-4680 h x ng/mL). The half-life of ACP-103 was approximately 55 hours, with a t(max) at 6 hours. ACP-103 was well tolerated at single doses up to and including 300 mg and multiple doses up to 100 mg once daily for 14 days.